Acupuncture treatments for infantile colic: a systematic review and individual patient data meta-analysis of blinding test validated randomised controlled trials. (2nd January 2018) - Skjeie, Holgeir; Skonnord, Trygve; Brekke, Mette; Klovning, Atle; Fetveit, Arne; Landgren, Kajsa; Hallström, Inger Kristensson; Brurberg, Kjetil Gundro
Abstract: Objective: Needle acupuncture in small children has gained some acceptance in Western medicine. It is controversial, as infants and toddlers are unable to consent to treatment. We aimed to assess its efficacy for treating infantile colic. Design: A systematic review and a blinding-test validation based on individual patient data from randomised controlled trials. Primary end-points were crying time at mid-treatment, at the end of treatment and at a 1-month follow-up. A 30-min mean difference (MD) in crying time between acupuncture and control was predefined as a clinically important difference. Pearson's chi-squared test and the James and Bang indices were used to test the success of blinding of the outcome assessors [parents]. Eligibility criteria and data sources: We included randomised controlled trials of acupuncture treatments of infantile colic. Systematic searches were conducted in Cochrane CENTRAL, MEDLINE, EMBASE, CINAHL and AMED, and in the Chinese language databases CNKI, VIP, Wang fang, SinoMed and Chinese Clinical Trial Registry. Results: We included three randomised controlled trials with data from 307 participants. Only one of the included trials obtained a successful blinding of the outcome assessors in both the acupuncture and control groups. The MD in crying time between acupuncture intervention and no acupuncture control was −24.9 min [95% confidence interval, CI −46.2 to −3.6; three trials] at mid-treatment, −11.4 min [95% CI −31.8 to 9.0; three trials] at the end of treatment and −11.8 min [95% CI −62.9 to 39.2; one trial] at the 4-week follow-up. The corresponding standardised mean differences [SMDs] were −0.23 [95% CI −0.42 to −0.06], −0.10 [95% CI −0.29 to 0.08] and −0.09 [95% CI −0.48 to 0.30]. The heterogeneity was negligible in all analyses. The statistically significant result at mid-treatment was lost when excluding the apparently unblinded study in a sensitivity analysis: MD −13.8 min [95%CI −37.5 to 9.9] and SMD −0.13 [95%CI −0.35 to 0.09]. The registration of crying during treatment suggested more crying during acupuncture [odds ratio 7.7; 95% CI 2.7–20.6; one trial].GRADE- Moderate quality evidence. Conclusions: Percutaneous needle acupuncture treatments should not be recommended for infantile colic on a general basis. Systematic review registration: PROSPERO 2015:CRD42015023253 Key points: The role of acupuncture in the treatment of infantile colic is controversial. Available trials are small and present conflicting results. There were no clinically important differences between infants receiving acupuncture and no acupuncture control in this IPD meta-analysis of randomised controlled trials. The data indicate that acupuncture induces some treatment pain in many of the children. The study results indicate that percutaneous needle acupuncture should not be recommended for treatment of infantile colic on a general basis.